A Final Reply to Hutchison and Loomis - Proffitt, Dennis R.; Stefanucci, Jeanine; Banton, Tom; Epstein, William (The Spanish Journal of Psychology, 2006)
While acknowledging that their design and methods were different from the original Proffitt, Stefanucci, Banton, and Epstein (2003) study, Hutchison and Loomis (H&L) continue to argue that their findings qualify our account of energetic influences on distance perception. This reply provides a brief and focused discussion of the methodological differences between their study and ours and why these differences were likely responsible for the different results. It is also argued that the measures employed by H&L are assessments of apparent location, not apparent distance.
Keywords: Distance perception; Spatial perception; Energetics; Perceived location; Intention